Short Telomere Length in Plasma of Sudanese Patients with Hepatocellular Carcinoma and Chronic Liver Diseases - Fayza A. Rahamtalla; Iman M. Shammat; Salma B. M. Mudawi; Maram Abbas; Mohammed A. H. Kheir Elsid; Mohammed S. M. Abdalla (Sudan Journal of Medical Sciences)
Background: Telomeres, a protective sequence of DNA at the end of chromosomes, are essential for the maintenance of chromosomal integrity and stability. With each cell division, telomeres are shortened until a critical length is reached. Several cancers have been linked to shortened telomere length (TL). The current cross-sectional study aims to investigate the TL in the plasma of Sudanese patients with hepatocellular carcinoma (HCC) and chronic liver diseases (CLD). Methods: Blood samples were obtained from 113 patients with HCC and CLD as well as from 50 healthy controls. The assessment of TL in blood samples was carried out using the relative quantitative PCR method. Results: Patients with HCC had significantly shorter TL than healthy controls (0.66 vs 0.89; P < 0.01), whereas insignificant shorter TL was detected in HCC patients as compared to those with CLD. A significant decrease in telomeres copy numbers was observed in HCC patients when compared to those with CLD (P < 0.01). Conclusion: The results of the present study demonstrate that TL is shorter in patients with HCC and CLD compared to healthy controls.